Identification and recognition of hazards in the work environment in welding workshops - Merry Sunaryo; Moch Sahri; Ratna Ayu Ratriwardhani; Farid Willy Kurnia (UNUSA Press, 2026)
The workplace is a place in which there are workers or the environment that is often entered by many workers who also intersect with sources of danger. The high number of work accident cases shows that there is still a lack of awareness of workers and companies in handling work safety issues. The welding workshop is one of the workplaces in the informal industry that needs attention in the implementation Occupational Safety and Health (OSH) in the workplace. Therefore, it is necessary to identify and recognize hazards in the work environment carried out by the welding workshop. The implementation of identification and recognition of hazards in the work environment was carried out on the welding workshop Jl. Jemur Ngawingan, the city of Surabaya. Activities have the main target is workers. The number of workers who became respondents was a total of 8 people. The implementation method carried out is identification and socialization related to the risk of hazards in the workplace, using poster media. The understanding given to workers is Knowledge of Occupational Safety and Health (OSH), Knowledge of the risk of hazards in the workplace, and the Importance of Using PPE (Personal Protective Equipment). There is an increase in workers' knowledge based on the results of the pretest and post test conducted. So that most workers understand the importance of implementing OSH, hazards in the work environment, to the importance of using appropriate PPE (personal protective equipment). Furthermore, it is necessary to do a deeper understanding of OSH, especially in occupational health. Workers need to know more about what hazard factors exist in the environment they work in and how to overcome them.